1998
DOI: 10.1046/j.1365-8711.1998.01918.x
|View full text |Cite
|
Sign up to set email alerts
|

Dark matter haloes within clusters

Abstract: We examine the properties of dark matter haloes within a rich galaxy cluster using a high‐resolution simulation that captures the cosmological context of a cold dark matter universe. The mass and force resolution permit the resolution of 150 haloes with circular velocities larger than 80 km s−1 within the cluster virial radius of 2 Mpc (with Hubble constant H0 = 50 km s−1 Mpc−1). This enables an unprecedented study of the statistical properties of a large sample of dark matter haloes evolving in a dense enviro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

66
579
5
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 472 publications
(651 citation statements)
references
References 15 publications
66
579
5
1
Order By: Relevance
“…(Merritt 1984;Ghigna et al 1998). The tidal effects are strongest near the cluster core radius and the approximation r tidal r peri σ halo /σ clus for the tidal radius is found to work well.…”
Section: Fig 14mentioning
confidence: 99%
“…(Merritt 1984;Ghigna et al 1998). The tidal effects are strongest near the cluster core radius and the approximation r tidal r peri σ halo /σ clus for the tidal radius is found to work well.…”
Section: Fig 14mentioning
confidence: 99%
“…Since this proposal was put forward, it has been established that typical orbits in N-body simulations of dark matter halos are rather elliptical (see, e.g., [32]) so that M (r) changes around the orbit and M (r)r is no longer an adiabatic invariant. It has therefore been pointed out by Gnedin et al [12] that the relation in Eq.…”
Section: Testing Adiabatic Contractionmentioning
confidence: 99%
“…Depending on the way the source is defined, subhalo finders can be broadly categorized into three types: configuration space finders that examine the spatial clustering of particles (e.g., Springel et al 2001; Knollmann & Knebe 2009;Ghigna et al 1998); phase space finders that con-sider clustering in both spatial and velocity space (e.g., Elahi et al 2011;Behroozi et al 2013;Maciejewski et al 2009); and tracking finders that build the source from past progenitors (Tormen et al 1998;Han et al 2012). It has been shown that configuration space finders suffer from a "blending" problem, the difficulty of resolving subhalos embedded in the inner high density region of the host halo due to spatial overlap (Muldrew et al 2011;Knebe et al 2011;Han et al 2012).…”
Section: Introductionmentioning
confidence: 99%